ACO/ARO/AIO-22 – External beam radiotherapy combined with endorectal high-dose-rate brachytherapy in elderly and frail patients with rectal cancer: A prospective multicentre trial of the German Rectal Cancer Study Group - Dapper, Hendrik; Fleischmann, Maximilian; Tselis, Nikolaos; Diefenhardt, Markus; Hofheinz, Ralf Dieter; Weiß, Christian; Grabenbauer, Gerhard G.; Merten, Ricarda; Grosu, Anca Ligia; Kirste, Simon; Rieken, Stefan; Claßen, Johannes; et al. (Clinical and Translational Radiation Oncology, 2025)
Purpose: Rectal cancer disproportionately affects the elderly population, with more than half of cases diagnosed in individuals aged 70 years or older. Frail patients in this group often face significant challenges tolerating the standard treatment of total mesorectal excision (TME), due to elevated risks of surgical complications and perioperative morbidity. Advances in radiotherapy techniques offer a viable alternative, providing effective tumor control while minimizing treatment-related toxicity. Recent clinical trials, including OPERA and MORPEUS, have demonstrated that dose-escalated radiotherapy, which integrates external beam (chemo)radiotherapy (EBRT) with high-dose-rate endorectal brachytherapy (HDR-BT) or contact X-ray brachytherapy (CXB), can achieve high clinical response rates and facilitate organ preservation in younger, healthier patient cohorts. Building on these findings, the ACO/ARO/AIO-22 study seeks to adapt these innovative approaches to meet the needs of elderly and frail patients with rectal cancer. Methods/Design: The ACO/ARO/AIO-22 trial is a prospective multicentre controlled trial. Elderly (age ≥70 years) and/or frail patients with non-metastatic rectal adenocarcinoma (cT1-3d N0/+ M0, mrCRM − / +) localized 0–16 cm from the ano-cutaneous line, unable to undergo radical surgery can be included. The initial treatment comprises an external beam radiation (EBRT) regime with 13 × 3 Gy (total: 39 Gy) over a period of two and a half weeks. Following initial restaging 6.5 weeks after completion of EBRT, endorectal HDR-BT will be delivered with 3 weekly fractions of 8 Gy to a total dose of 24 Gy (prescribed at the radial margin of the tumor; with a maximum prescription depth of 10 mm); alternatively, with CXB with 90 Gy in 3 weekly fractions. The primary objective is complete or near complete clinical response (cCR or ncCR) and the second primary endpoint is quality of life (QoL) measured with the EORTC QLQ-ELD14, both at 12 months after treatment start. Discussion: The ACO/ARO/AIO-22 prospective multicentre trial will evaluate organ preservation rates and QoL after combining EBRT with endorectal HDR-BT in elderly and/or frail patients with rectal cancer. Trial Registration: Clinicialtrials.gov number: NCT06729645.
CRIS-Team Scopus Importer:2025-04-25

Assessment of needle bending and tracking requirements for optimized needle placement in combined intracavitary/interstitial gynecologic brachytherapy - Karius, Andre; Strnad, Vratislav; Lotter, Michael; Kreppner, Stephan; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Schweizer, Claudia (Strahlentherapie und Onkologie, 2025)
Purpose: Needle tracking using external prediction techniques such as optical tracking is a modern approach aimed at improving implantation accuracy in gynecologic brachytherapy. This study aims to investigate the corresponding impact of needle bending in situ and to analyze needle path deviations from the intended locations occurring in our current clinical workflow that only considers ultrasound imaging without tracking. Methods: We developed a semi-automated approach for reconstructing brachytherapy needles based on planning CTs and compared the respective accuracy to the also determined intra-observer variability of manual reconstructions. Based on this, we measured needle bending in situ for 89 patients and calculated the Euclidean distances between actual needle tips and needle tip predictions both longitudinally and laterally to the insertion direction. Furthermore, we compared actual and intended spacings between inserted needles to estimate implantation uncertainties with respect to our current clinical workflow. Results: Our developed reconstruction featured an accuracy of 0.17 ± 0.08 mm, which was improved compared to the intra-observer variability of 0.21 ± 0.11 mm. Needle bending depended strongly on needle length and ranged from 3.6 ± 2.1 mm for 100–120 mm needles up to 7.9 ± 3.0 mm for 200–220 mm needles. Deflections in the transverse direction were substantially higher than tip deviations in the longitudinal direction. Furthermore, we found deviations from an equidistant spacing between needle paths of 1.4 ± 1.2 mm in the transverse direction. Conclusion: Inserting brachytherapy needles can be substantially affected by transverse needle bending in situ, which should therefore be corrected for in prediction approaches such as optical tracking.
CRIS-Team Scopus Importer:2025-02-21
Keywords: Adaptive brachytherapy; Image guidance; Intraoperative navigation; Needle displacement; Optical infrared tracking

Balancing barriers: Family, career, and gender equality in radiation oncology and radiation research—An interdisciplinary prospective survey among the young workforce - Trommer, Maike; Grohmann, Maximilian; Fabian, Alexander; Ehret, Felix; Hess, Julia; Rückert, Michael; Matschke, Johann; Stefanowicz, Sarah; Rühle, Alexander; Ferdinandus, Simone; Merten, Ricarda; Besserer, Angela; et al. (Strahlentherapie und Onkologie, 2025)
Purpose: There is an urgent need to recruit and retain young professionals in radiation oncology and radiation research as the healthcare system faces major challenges. Our study investigated the experiences and needs of young professionals in this field, focusing on the impact of unpaid care work and gender-related issues. Methods: A web-based survey was created and distributed over a six-week period, featuring one general questionnaire along with three occupation-specific versions tailored for physicians, biologists, and medical physicists involved in radiation oncology and research. Results: Most participants with care responsibilities have temporary contracts, especially female physicians and biologists, while female medical physicists are more likely to hold permanent positions. Research is often conducted outside regular hours, with limited cover arrangements and part-time options varying by field. Key career risks include economic pressure, work-life balance, and uncertain contracts, with employees with care duties feeling less supported overall. In addition, men seem to be more involved in care work and thus face unique challenges, such as insufficient career support and fears of poor future perspective. The study emphasizes the need for strategies to address relevant issues, such as flexible working arrangements, better mentoring support, and clear substitution policies that can ensure that young professionals can balance caring responsibilities with work and career demands. Conclusion: Addressing these challenges is critical for sustaining a diverse and qualified workforce in radiation oncology and radiation research, ensuring excellence in patient care and scientific progress.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Gender; Parity; Radiation oncology; Survey; Young workforce

Brachytherapy in vaginal cancer for organ preservation: Clinical outcome and safety from a single center experience - Merten, Ricarda; Strnad, Vratislav; Karius, Andre; Lotter, Michael; Kreppner, Stephan; Schweizer, Claudia; Fietkau, Rainer; Schubert, Philipp (Gynecologic Oncology, 2024)
Background: Interstitial and/or intracavitary brachytherapy is an integral part of the treatment of vaginal cancer Brachytherapy (BT) has shown to improve local control, overall survival (OS) and disease-free survival (DFS). The aim of our study was to analyze the efficacy and safety of brachytherapy in patients with vaginal cancer. Materials and methods: Between 2000 and 2023, 27 patients with vaginal cancer in stage FIGO I-III were treated with brachytherapy with or without external beam radiotherapy (EBRT) and simultaneous chemotherapy. Brachytherapy has been performed either as PDR-brachytherapy alone with a median cumulative dose up to 62.5 Gy (EQD2 = 63.9 Gy) or with PDR-BT boost with median dose of 30.9 Gy (EQD2 = 30.4 Gy). HDR-BT was administered solely as boost with a median dose of 25.5 Gy (EQD2 = 47.8 Gy). The median dose of EBRT was 48.7 Gy and 49.4 Gy for primary and for pelvic lymph nodes. Results: Median follow-up was 39 months (2−120). 5/27 patients developed local recurrences and the 5-year cumulative local recurrence rate for whole patient population was 18.5%. 5-year OS and DFS was 90% and 68%. 5-year DFS for Stage I-II was 72% and for Stage III 65% (p = 0.933). Grade 3 late side effects of brachytherapy were documented in 3/22 patients (13.6%), one patient experienced Grade 4 toxicity (4.5%). Conclusion: Brachytherapy with or without EBRT and concomitant chemotherapy for vaginal cancer is a safe and effective treatment option with excellent local control and overall survival and acceptable toxicity.
CRIS-Team Scopus Importer:2024-08-23
Keywords: Brachytherapy; Dose-escalation; Organ-sparing; Vaginal cancer

Comparison of dose calculation approaches and clinical dose–response in image-guided head&neck brachytherapy of the oral cavity - Schaller, Sabrina; Strnad, Vratislav; Schweizer, Claudia; Lubgan, Dorota; Merten, Ricarda; Fietkau, Rainer; Bert, Christoph; Karius, Andre (Clinical and Translational Radiation Oncology, 2025)
Purpose: Model-based dose calculation algorithms (MBDCAs) are increasingly applied in brachytherapy, but their considerations in dose–response analyses is still lacking. This study aimed to assess correlations between both TG-43 and MBDCA dosimetry and reports on clinical outcomes for oral cavity brachytherapy. Methods: We considered 158 patients with oral cavity cancer treated in our institution between 2012 and 2021. Survival outcomes and toxicity (soft tissue necrosis, osteoradionecrosis, mucositis, xerostomia) were reported for a median follow-up of 80 months (2–152 months). All clinical, TG-43 based treatment plans were re-calculated using a MBDCA integrated into our planning system. Differences considering several target volume, tissue, and bone dose parameters were evaluated. Parameter correlations with clinical outcomes and thresholds associated with increased toxicity were investigated. Results: Cumulative local recurrence, soft-tissue necrosis, osteoradionecrosis, mucositis, and xerostomia rate were 21 %, 22 %, 28 % and 79 % considering all patients. Substantial differences between MBDCA and TG-43 were observed, especially regarding high-dose areas with changes up to 19 %. A number of dose-toxicity correlations were observed, as for osteoradionecrosis (1.6 % vs. 10.3 % for bone D2ccm ≥ 59.3 Gy), soft tissue necrosis (16 % vs. 32 % for tissue D5ccm ≥ 87.7 Gy), and local recurrence (13 % vs. 25 % for dose non-uniformity ratio < 0.29) (using the MBDCA). Target volumes ≥ 10.2–11.8ccm were associated with increased rates of soft tissue necrosis and mucositis. Dosimetric thresholds and correlations differed between TG-43 and MBDCA. Conclusion: For oral cavity brachytherapy, several important dosimetric thresholds associated with increased toxicity were determined. MBDCAs for corresponding dose calculations should be advanced and used in clinical practice.
CRIS-Team Scopus Importer:2025-05-16

Definitive treatment for primary urethral cancer: A single institution's experience with organ-preserving brachytherapy - Merten, Ricarda; Strnad, Vratislav; Karius, Andre; Lotter, M.; Kreppner, Stephan; Schweizer, Claudia; Fietkau, Rainer; Schubert, Philipp (Brachytherapy, 2024)
BACKGROUND: Radical urethectomy ± cystectomy has long represented the standard of care for rare primary urethral cancer (PUC). With our analysis, we want to demonstrate the efficacy and safety of brachytherapy (BT) of urethra for organ preservation. MATERIALS AND METHODS: We analyzed treatment procedures and results of 3 patients with PUC, which have been treated in our department between 2011 and 2020 with brachytherapy. One male patient underwent brachytherapy with chemoradiotherapy after transurethral resection (TUR). Brachytherapy has been performed as high-dose-rate (HDR) boost with a cumulative dose of 8 Gy (9.3 Gy EQD2-α/β = 10 Gy). The 2 further female patients have been treated with sole pulsed-dose-rate (PDR) brachytherapy with a total dose of 49.9 Gy (50.3 Gy EQD2-α/β = 10 Gy) and 62.2 Gy (64.6 Gy EQD2-α/β = 10 Gy). RESULTS: Median follow-up was 103 months (41–153). No local recurrence occurred and all patients are still alive. For the male patient we documented Grade 3 cystitis. As late side effects the pre-existing Grade 2 incontinence worsened to Grade 3. Among female patients one developed Grade 3 vaginal synechiae. There was no Grade ≥4 toxicity. CONCLUSION: Brachytherapy in PUC is a feasible and promising option with high local control rate and tolerable toxicity. It provides a good alternative to surgery for organ preservation in selected patients.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Brachytherapy; Dose-escalation; Organ-preservation; Primary urethral cancer

Dose Reduction in the Swallowing Area by De-intensification of Radiotherapy in Patients with Head and Neck Cancer in the postoperative Situation - first Plan Analyzes of the DIREKHT Study - Haderlein, Marlen; Speer, Stefan; Hecht, Markus; Merten, Ricarda; Scherl, C.; Semrau, S.; Ott, O.; Fietkau, Rainer (2018)
EVALuna2:36499

Establishing an intraoperative, mobile CBCT-based workflow for gynecologic brachytherapy: primary experience and benefit assessment - Karius, Andre; Strnad, Vratislav; Bert, Christoph; Fietkau, Rainer; Merten, Ricarda; Schweizer, Claudia (Frontiers in Oncology, 2025)
Background and purpose: In the brachytherapy of cervical cancer, creating a suitable implant based on ultrasound guidance may be impacted by imaging limitations. To validate the implant if ultrasound is not sufficient, we implemented a new workflow utilizing additional intraoperative cone-beam computed tomography (CBCT). The aims of this work were to describe the newly established workflow, reflect associated (dis)advantages, and assess geometric and dosimetric benefits compared to the previous solely ultrasound-guided workflow. Materials and methods: We report the establishment of our new workflow utilizing mobile CBCT during interventions and corresponding experiences for 26 consecutive patients. Image quality was assessed by considering the applicator visualization and contrast–noise ratio (CNR) between tissues. Implant changes based on CBCT scans were analyzed with respect to the enhanced insertion depths (EIDs) of needles and their tip distances to target volume borders. Dosimetric effects were evaluated by calculating common dose–volume parameters for target volume and organs at risk (OARs) and comparing them in both a previous patient cohort and scenarios simulating sole ultrasound guidance. Implant uncertainties between intra- and postoperative imaging were analyzed using a corresponding registration as well. Results: Implementing intraoperative CBCT was associated with clinical challenges but increased safety feeling during interventions and resulted in geometric as well as dosimetric benefits. Needles could be shifted deeper into the pelvis by an EID of 14 ± 11 mm based on CBCT, associated with corresponding significant dose improvements for target volume and OARs with a mean tradeoff increase of up to 4.8 Gy. With a reasonable CNR between tissues up to 8.5 ± 3.6 and clear detectability of applicators, image quality was sufficient to fulfill intraoperative intentions. Furthermore, the CBCT scans were suitable for treatment planning purposes from a geometric uncertainty perspective. Conclusion: The implementation of intraoperative CBCT can substantially improve the quality and safety of image-guided gynecologic brachytherapy.
CRIS-Team Scopus Importer:2025-05-09
Keywords: adaptive brachytherapy; image-guidance; interventional radiotherapy; intraoperative imaging; mobile CT

How Octogenarians with Bladder Cancer Are Treated in a Maximum-Care Hospital: The Real-Life Experience - Sikic, Danijel; Wach, Sven; Taubert, Helge; Richterstetter, Mario; Kunath, Frank; Lieb, Verena; Krause, F. Steffen; Merten, Ricarda; Ott, Oliver; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (Urologia Internationalis, 2016)
With increasing life expectancy, curative treatment of octogenarians with urothelial carcinoma of the bladder (UCB) becomes more important.The treatment modalities of 276 octogenarians with UCB who were treated at the University Hospital of Erlangen between 1982 and 2011 were assessed retrospectively.One hundred forty-six patients had non-muscle invasive bladder cancer (NMIBC) while 71 had muscle invasive bladder cancer (MIBC). No data was available for 59 patients. Eighty-five (58.2%) of the 146 patients with NMIBC received transurethral resection of the bladder tumor (TURBT) only, another 38 patients (26%) underwent additional intravesical therapy; and 8.9% were treated with radiochemotherapy (RCT), 4.1% with radiotherapy (RT), 1.4% with systemic chemotherapy and 1.4% with radical cystectomy (RC). Of the 71 patients suffering from MIBC, 39 (54.9%) received TURBT alone. A potentially curative therapy was performed on 31 of the 71 patients with MIBC (43.7%). Of these, 16 patients (51.6%) received RCT, 9 patients (29.0%) RT and 6 patients (19.4%) RC. In Kaplan-Meier analysis, patients with MIBC had better median overall survival with curative treatment compared to TURBT alone (28 vs. 9 months; p < 0.001, log-rank test).By offering a wide range of treatment options, over 43% of octogenarians with MIBC received a curative therapy at a maximum care hospital.
EVALuna2:16292

Increased skin and mucosal toxicity in the combination of vemurafenib with radiation therapy - Merten, Ricarda; Hecht, Markus; Haderlein, Marlen; Distel, Luitpold; Fietkau, Rainer; Heinzerling, Lucie; Semrau, Sabine (Strahlentherapie und Onkologie, 2014)
Palliative radiotherapy is often required for patients with metastatic malignant melanoma in the case of bone or brain metastases. Since BRAF inhibitor therapy is highly efficient in V600-mutated melanomas, there is hesitation to stop it during radiotherapy. Consequently, radiotherapy under simultaneous vemurafenib treatment is frequently needed.We report the case of a patient receiving palliative radiotherapy of spinal bone metastases before and during vemurafenib therapy. The skin reactions were quantitatively scored using computer-assisted digital image evaluation.Radiotherapy without vemurafenib was tolerated very well, whereas radiotherapy under simultaneous vemurafenib treatment resulted in accentuated skin reactions. Furthermore, the patient developed dysphagia and had to be hospitalized for parenteral nutrition. In the quantitative analysis, there was a twofold increase in pigmentation and erythema of the irradiated skin area of the thoracic spine when vemurafenib was combined with radiotherapy compared with radiotherapy treatment alone. This is the first reported case of a patient showing no complications during radiotherapy without vemurafenib but remarkable skin and mucosal toxicity under concurrent vemurafenib therapy. Thus, a genetically conditioned individually elevated radiosensitivity can definitely be excluded. Compared with other reported cases, radiosensitization was not limited to the skin, but also affected the esophageal mucosa.Vemurafenib is a strong radiosensitizer. Patients receiving radiotherapy under simultaneous vemurafenib treatment should be monitored very closely.
EVALuna2:18209

Is model-based dose calculation based on cone-beam computed tomography suitable for adaptive treatment planning in brachytherapy? - Karius, Andre; Shariff, Maya; Schaller, Sabrina; Lotter, Michael; Strnad, Vratislav; Lackner, Niklas; Fietkau, Rainer; Bert, Christoph; Merten, Ricarda; Schweizer, Claudia (Strahlentherapie und Onkologie, 2024)
Background and purpose: Model-based dose calculation considering tissue compositions is increasingly being investigated in brachytherapy. The aim of this study was to assess the suitability of modern cone-beam computed tomography (CBCT) imaging compared to conventional computed tomography (CT) scans for this purpose. Materials and methods: By means of a phantom study, we evaluated the CT numbers and electron densities measured using a modern CBCT device as well as a conventional CT scanner for various materials. Based on this, we compared dose calculations (using the TG-43 formalism as well as model-based collapsed cone calculations assuming uniform materials [ACEuniform] and considering CT numbers [ACECT#]) on planning CTs and control CBCTs for patients with cervical and breast cancer as well as phantom-simulated skin cancer cases. Assessing dosimetric deviations between the planning CTs and control CBCTs acquired during the treatment course served to estimate interfractional implant variations. Results: The comparison of ACEuniform–ACECT# deviations between planning CTs and control CBCTs revealed no statistically significant difference for almost all examined dose parameters. Dosimetric deviations between model-based dose calculations and TG-43 were partly significant but of small magnitude (< 10 cGy per fraction). Interfractional dosimetric variations were substantially larger than the dosimetric differences found between the various dose calculation procedures. Conclusion: Model-based dose calculation based on modern CBCT imaging was suitable. However, the found differences between these calculations and the TG-43 formalism should be investigated in dose–outcome analyses. The observed interfractional dosimetric variations revealed the importance of performing treatment quality assurance.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Adaptive radiotherapy; Brachytherapy; Breast cancer; Cervical cancer; Model-based dose calculation

Lipiodol injections for optimization of target volume delineation in a patient with a second tumor of the oropharynx: A case report - Haderlein, Marlen; Merten, Ricarda; Stojanovic, Andrea; Speer, Stefan; Scherl, Claudia; Fietkau, Rainer; Ott, Oliver J. (Strahlentherapie und Onkologie, 2015)
Lipiodol injections were administered in the head and neck area to improve gross tumor volume (GTV) definition for small-volume re-irradiation of a 63-year-old previously irradiated patient with a second tumor of the oropharynx in the posterior wall with longitudinal ligament infiltration (cT4cN0cM0).The patient had dialysis-depending renal failure. On diagnostic computed tomography (CT), which was performed with intravenous contrast agent, the tumor in the oropharynx was not detectable. Because of dialysis-depending renal failure comorbidity, no contrast agent was applied in the planning CT and in the diagnostic magnetic resonance imaging (MRI) study. In each cross-sectional imaging study performed, the GTV, especially in craniocaudal extensions, was not safely delineable. Therefore, craniocaudal tumor margins were pharyngoscopically marked with Lipiodol injections, an iodine-containing contrast agent.In a second planning CT, the GTV could be defined with the help of the Lipiodol marks and small-volume re-irradiation was performed. No Lipiodol-associated side effects occurred in the patient.In the present case, the use of Lipiodol injections at the tumor margins facilitated the definition of the GTV.
EVALuna2:18277

Locoregional recurrence in anal cancer: risk factors and management strategies - Gryc, Thomas; Putz, Florian; Merten, Ricarda; Goerig, Nicole; Fietkau, Rainer; Strnad, Vratislav (2017)
EVALuna2:32883

Long-Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High-Risk Bladder Cancer (Ta, Tis, T1, T2) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al. (Oncologist, 2019)
Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high-risk bladder cancer after transurethral resection of bladder tumor (TUR-BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR-BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR-BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p =.037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p =.092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p =.045). Five-year OS from unadjusted Kaplan-Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5-year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p =.0001). RCT + RHT compared with RCT showed a significantly better bladder-preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p =.006). Median follow-up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR-BT followed by RT; concomitant platinum-based chemotherapy combined with RHT in patients with high-grade bladder cancer improves local control, bladder-preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle-invasive bladder cancer in medically fit patients, despite many centers reporting excellent long-term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder-preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum-based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder-preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Bladder cancer; Bladder preservation; Chemoradiotherapy; Hyperthermia; Radiotherapy

Micropapillary morphology is an indicator of poor prognosis in patients with urothelial carcinoma treated with transurethral resection and radiochemotherapy - Bertz, Simone; Wach, S.; Taubert, Helge; Merten, Ricarda; Krause, F. S.; Schick, S.; Ott, O. J.; Weigert, E.; Dworak, O.; Roedel, C.; Fietkau, Rainer; Wullich, Bernd; et al. (Virchows Archiv, 2016)
Purpose of this study was to evaluate prognostic impact of rare variants of urothelial bladder cancer (BC) after treatment with combined radiochemotherapy (RCT). To this end tumour tissue of 238 patients with urothelial carcinoma (UC) treated with transurethral resection of the bladder (TUR-B) and RCT with curative intent was collected. Histomorphological analysis included re-evaluation and semi-quantitative assessment of rare UC subtypes. Additionally, human epidermal growth factor receptor 2 (HER2) chromogenic in situ hybridisation (CISH) was performed in tumours with a micropapillary component exceeding 30 %. Long-term follow-up was available for 200 patients (range 3-282 months). Variant UC histology was found in 45 of 238 tumours, most frequently micropapillary UC (N = 17) including cases with a small fraction of tumour with micropapillary morphology. The mere presence of micropapillary morphology did not affect prognosis. In tumours with extensive (>=30 %) micropapillary morphology (N = 8) Kaplan-Meier analysis revealed significantly worse cancer specific survival (CSS) (P = 0.002) compared to conventional UC (mean survival times 97 months and 229 months, respectively). Univariate Cox regression analysis of cases with >=30 % micropapillary morphology revealed a hazard ratio of 4.726 (95 % CI 1.629-13.714) for CSS (P = 0.004). CISH revealed HER2 gene amplification in 3/10 tumours with >=30 % micropapillary component. In conclusion, for BC treated with TUR-B and RCT, the presence of micropapillary morphology in more than 30 % of the tumour is an adverse prognostic factor. Further studies are needed to evaluate a potential benefit of different, especially multimodal treatment strategies for micropapillary UC and also other subtypes of UC. Her2 represents a promising therapeutic target in a subset of micropapillary UC.
EVALuna2:6800

Outcomes of I-125 Low-Dose-Rate Brachytherapy in Patients with Localized Prostate Cancer: A Comprehensive Analysis from a Specialized Tertiary Referral Center - Schubert, Philipp; Strnad, Vratislav; Höfler, Daniel; Schweizer, Claudia; Putz, Florian; Lotter, Michael; Kreppner, Stephan; Karius, Andre; Fietkau, Rainer; Merten, Ricarda (Journal of Personalized Medicine, 2024)
Low-dose-rate (LDR) brachytherapy with I-125 seeds is one of the most common primary tumor treatments for low-risk and low-intermediate-risk prostate cancer. This report aimed to present an analysis of single-institution long-term results. We analyzed the treatment outcomes of 119 patients with low- and intermediate-risk prostate cancer treated with LDR brachytherapy at our institution between 2014 and 2020. The analysis focused on biochemical recurrence rates (BRFS), overall survival (OS), cumulative local recurrence rate (CLRR), and the incidence of acute and late toxicities. Patient-reported quality of life measures were also evaluated to provide a holistic view on the treatment’s impact. The median follow-up period was 46 months. CLRR was 3.3% (4/119), five-year BRFS was 87%, and the five-year OS rate was 95%. Dysuria was the most common acute urinary toxicity, reported in 26.0% of patients as grade 1 and 13.4% as grade 2. As a late side effect, 12.6% of patients experienced mild dysuria. Sexual dysfunction persisted in 6.7% of patients as grade 1, 7.5% as grade 2, and 10.0% as grade 3. LDR brachytherapy in patients with prostate cancer is an effective treatment, with favorable clinical outcomes and manageable toxicity. The low CLRR and high OS rates, as well as low incidence of severe side effects, support the continued use of LDR brachytherapy as a primary treatment modality for localized prostate cancer.
CRIS-Team Scopus Importer:2024-09-06
Keywords: I-125 seeds; LDR brachytherapy; low-intermediate-risk prostate cancer; low-risk prostate cancer; patient-reported outcomes; prostate cancer; toxicity; treatment outcomes

Postoperative brachytherapy alone for 217 patients with early-stage oral cavity squamous cell carcinoma - Schweizer, Claudia; Strnad, Vratislav; Lotter, M.; Kreppner, Stephan; Merten, Ricarda; Fietkau, Rainer; Karius, Andre (Clinical and Translational Radiation Oncology, 2025)
Introduction: Postoperative radiotherapy is generally recommended for pT1/2pN0 squamous cell carcinoma of the oral cavity (OSCC) if risk factors are present. Prospective studies are missing. Interventional radiotherapy offers a precise dose application. In this paper we analyze long-term efficacy and toxicity in a large single-center cohort of patients with early OSCC receiving sole postoperative brachytherapy (BT). Material and methods: From 1998 to 2023, 217 patients were postoperatively treated with sole BT in our institute. The median follow-up was 110 months (range: 2–316). The primary objective was local control. Secondary outcomes were overall survival, cancer specific survival, and toxicity. Results: The local recurrence rates for 12, 24, and 60 months were 7.1 %, 9.1 %, and 12.6 %. The disease-free survival was 89.7 %, 86.1 %, and 79.3 %. The overall survival rates at 12, 24, and 60 months were 94.4 %, 89.6 %, and 77.9 %. The cancer-specific survival was 97.1 %, 96.6 %, and 92.9 %, respectively. At two years, the rate of regional recurrence was 8.3 %. Patients without neck dissection had a significantly increased risk for lymph node recurrence (p = 0.025). Side effects ≥ grade 3 were seen in 14 % (30/217). 17 % (37/217) of patients developed a soft tissue necrosis (STN). Osteoradionecrosis (ORN) was seen in 7 % (15/217) of patients. A target volume > 15 cm3 was significantly associated with the occurrence of STN (p = 0.011) and ORN (p = 0.004). Conclusions: Postoperative interventional radiotherapy for previously not irradiated patients with early-stage OSCC is a safe and efficient treatment. Randomized trials are needed to compare these results to omission of postoperative radiotherapy as well as external beam radiotherapy.
CRIS-Team Scopus Importer:2025-01-31
Keywords: Early-stage oral cavity cancer; HDR; Interventional radiotherapy; Long-term toxicity after brachytherapy; PDR; Postoperative radiotherapy

Prostate brachytherapy boost: Long-term results of protocol-based treatment of patients with non-metastatic prostate cancer. - Schweizer, Claudia; Strnad, Vratislav; Merten, Ricarda; Schubert, Philipp; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Karius, Andre (Journal of Contemporary Brachytherapy, 2024)
PURPOSE: To evaluate the efficacy and toxicity of interstitial temporary brachytherapy boost for prostate cancer patients using real-world data. MATERIAL AND METHODS: Between 2008 and 2016, 115 patients treated with external beam radiotherapy (EBRT) followed by a brachytherapy boost (BT boost) were eligible for this retrospective analysis. Patients received either interstitial high-dose-rate brachytherapy (HDR-BT) with 2 x 9-9.5 Gray (Gy) schedule or pulsed-dose-rate brachytherapy (PDR-BT) with 35 Gy as boost after EBRT (50.4 Gy), up to a total dose of 86-98 Gy (EQD2α/β = 3). Primary endpoints of the present analysis were cumulative local recurrence rate (LRR), biochemical recurrence-free survival (bRFS), tumor-specific survival, and overall survival (OS). As secondary objective, treatment-related toxicity was evaluated. RESULTS: The median follow-up time was 87 (range, 9-159) months, and the median age was 72 (range, 48-83) years. The median prostate specific antigen value (PSA) was 12.2 (range, 2.4-288) ng/ml. 78/115 (68%) patients had high-risk prostate cancer according to the D'Amico classification. At 7 years, the cumulative LRR for the whole cohort was 1.8%. The 7-year bRFS, cancer-specific survival, and OS were 85.2%, 97.3%, and 88.9%. The 5-year prevalence of late toxicity grade 3 or higher according to the LENT-SOMA scale was 4%. There were no significant differences for treatment outcome or toxicity for HDR vs. PDR treatment. A prostate gland of 50 cm3 or more was not associated with worse treatment efficacy or increased side effects, apart from the prevalence of urethritis after 5 years (p = 0.035). CONCLUSIONS: BT boost in patients with prostate cancer is efficient and well-tolerated, with low rates of side effects also in elderly patients. HDR- and PDR-BT were equally efficient and well-tolerated. A large prostate gland is no contraindication for BT. Therefore, BT boost should be offered to all eligible patients.
EVALuna2:595654

Regional deep hyperthermia: impact of observer variability in CT-based manual tissue segmentation on simulated temperature distribution - Aklan, Bassim; Hartmann, Josefin; Zink, Diana; Siavooshhaghighi, Hadi; Merten, Ricarda; Putz, Florian; Ott, Oliver; Fietkau, Rainer; Bert, Christoph (Physics in Medicine and Biology, 2017)
The aim of this study was to systematically investigate the influence of the inter- and intra-observer segmentation variation of tumors and organs at risk on the simulated temperature coverage of the target. CT scans of six patients with tumors in the pelvic region acquired for radiotherapy treatment planning were used for hyperthermia treatment planning. To study the effect of inter-observer variation, three observers manually segmented in the CT images of each patient the following structures: fat, muscle, bone and the bladder. The gross tumor volumes (GTV) were contoured by three radiation oncology residents and used as the hyperthermia target volumes. For intra-observer variation, one of the observers of each group contoured the structures of each patient three times with a time span of one week between the segmentations. Moreover, the impact of segmentation variations in organs at risk (OARs) between the three inter-observers was investigated on simulated temperature distributions using only one GTV. The spatial overlap between individual segmentations was assessed by the Dice similarity coefficient (DSC) and the mean surface distance (MSD). Additionally, the temperatures T90/T10 delivered to 90%/10% of the GTV, respectively, were assessed for each observer combination. The results of the segmentation similarity evaluation showed that the DSC of the inter-observer variation of fat, muscle, the bladder, bone and the target was 0.68 ± 0.12, 0.88 ± 0.05, 0.73 ± 0.14, 0.91 ± 0.04 and 0.64 ± 0.11, respectively. Similar results were found for the intra-observer variation. The MSD results were similar to the DSCs for both observer variations. A statistically significant difference (p < 0.05) was found for T90 and T10 in the predicted target temperature due to the observer variability. The conclusion is that intra- and inter-observer variations have a significant impact on the temperature coverage of the target. Furthermore, OARs, such as bone and the bladder, may essentially influence the homogeneity of the simulated target temperature distribution.
EVALuna2:32876

Safety and Efficacy of Brachytherapy in Inoperable Endometrial Cancer - Merten, Ricarda; Strnad, Vratislav; Schweizer, Claudia; Lotter, Michael; Kreppner, Stephan; Fietkau, Rainer; Schubert, Philipp; Karius, Andre; Schubert, Philipp (Journal of Personalized Medicine, 2024)
Background/Objectives: Radiotherapy represents the only treatment option for patients with inoperable endometrial cancer (EC). The aim of our study was to evaluate the efficacy and safety of brachytherapy (BT) in this selected patient population. Methods: Between 1990 and 2019, 18 patients with inoperable EC in stage FIGO I–IV were treated with intracavitary brachytherapy using the “Heyman Packing technique”. BT was performed either as sole PDR- or HDR-brachytherapy with a median cumulative dose up to 60.0 Gy (67.9 Gy EQD2 α/β = 3Gy) and 34.0 Gy (75.6 Gy EQD2 α/β = 3Gy), respectively. Results: The median follow-up was 46 months (6–219). The mean age was 71 years. The 5-year cumulative local recurrence rate (CLRR) for the whole cohort was 27.3%. The 5-year overall survival (OS), distant metastasis-free survival (DMFS), and disease-free survival (DFS) were 51%, 79%, and 69%. The 5-year DFS for low-, intermediate-, and high-risk EC was 89%, 50%, and 44% (p = 0.51). No significant difference in DFS was observed in patients over 70 (p = 0.526). No late side effects of grade > 1 were documented. Conclusions: Brachytherapy for inoperable EC is a safe and effective treatment option, offering good local control and OS with minimal toxicity. Moreover, brachytherapy effectively controls hemoglobin-relevant bleeding. Therefore, BT should be considered a viable alternative to non-curative treatment strategies in gynecological multidisciplinary conferences.
CRIS-Team Scopus Importer:2025-02-04
Keywords: brachytherapy; definitive treatment; endometrial cancer; hemostyptic irradiation; inoperable

The Treatment Reality of Octogenarians with Bladder Cancer in a Maximum Care Hospital - Sikic, D.; Wach, S.; Taubert, Helge; Richterstetter, M.; Kunath, F.; Lieb, V.; Krause, S.; Merten, Ricarda; Ott, O.; Fietkau, Rainer; Wullich, Bernd; Keck, Bastian (2016)
EVALuna2:18333